'Soya Milk Tris‐based Phytoextender Reduces Apoptosis in Cryopreserved Buffalo (Bubalus bubalis) Spermatozoa'. Issue 5 (12th August 2014) - Mohan, R; Atreja, SK
Contents The objective of this study was to investigate the effect of newly developed soya milk Tris (SMT)‐based phytoextender as an alternative to egg yolk Tris (EYT) extender used for cryopreservation of buffalo (Bubalus bubalis) spermatozoa on apoptosis. Fresh buffalo semen (control without dilution) was cryopreserved in conventional EYT (20% egg yolk v/v in Tris) and SMT (25% soya milk v/v in Tris) extender and used for the assessment of expression of apoptotic proteins. Proteins extracted from a total number of nine ejaculates from three individual buffalo bulls chosen at random were separated using SDS–PAGE followed by immunoblotting against caspase‐8, caspase‐9, caspase‐3, poly(ADP‐ribose)polymerase (PARP), cytochrome c and apoptosis inducing factor (AIF). In addition, fluorescence microscopy was used for the detection of mitochondrial membrane potential (JC‐1 assay) and apoptotic cells (annexin V‐FITC/PI assay). The results obtained clearly indicate the significant (p < 0.05) reduction in the expression of caspase‐3 (27 kDa), caspase‐8 (53 kDa), caspase‐9 (50 kDa) precursor and cytochrome c (17 kDa) in semen cryopreserved in SMT extender in comparison with EYT extender. A non‐significant (p > 0.05) reduction in expression of PARP‐DNA‐binding subunit (24 kDa) was observed in SMT extender. No expression of AIF was found in cryopreserved semen samples. A significant (p < 0.05) increase in the mean percentage of cells having high mitochondrial membrane potential and a non‐significant (p > 0.05) decrease in late apoptotic cells (AN+/PI+) was observed in SMT extender when compared to EYT extender. The results demonstrated that cryopreservation of buffalo semen in SMT‐based phytoextender can replace the traditional egg yolk extenders as it reduces the expression of apoptotic proteins maintaining high mitochondrial membrane potential and gives better protection to sperms in terms of its non‐animal origin.